Pertumbuhan Dan Perkembangan Akar Semai Mangrove Sejati Ceriops tagal (Perr.) C.B.Rob Pada Berbagai Salinitas - Marnida Uli Lubis; Mohammad Basyuni; Budi Utomo (Program studi Kehutanan USU, 2016)
The deforestation of mangrove caused by human activities to the effected the composition of mangrove forest stand. It is therefore needed for mangrove rehabilitation to restore mangrove ecosystem. Growth and root development of mangrove seedlings Ceriops tagal (Perr.) C.B.Rob under different salinity was studied in the greenhouse, Faculty of Agriculture, University of Sumatera Utara, started from 22nd May until 22nd November 2015. This study was aimed at determining the level of seedling growth and root development under C. tagal seedlings under different salinity. This research used the completely random design (CRD) with 5 treatment, namely 0%, 0,5%, 1,5%, 2%, and 3% for 10 replication. The best result showed that growth and seedlings development was obtained at 0,5% salinity, high growth of seedlings at 0,5%, diameter at 0,5%, number of leaf at 0,5%, leaf area at 0,5%, thick leaves at 0,5%, number of root at 0,5%, length roots at 2%, root diameter at 0,5%, the water content of the root 0%, the water content of the shoot 0,5%, and the ratio of root and shoot at 0,5%. Keywords : Mangrove, Ceriops tagal, salinity, root